(untitled) (KULT_online, 2019)
Based on a joint project of Slavists from Prague and Germanists from Göteborg, this volume treats problems of the transfer of empirical knowledge in the border area between fictional and pragmatic literature. Equally divided between German and Slavic topics, the twelve contributions deal mostly with a body of individual works of predominantly 20th-century authors from Germany, Russia, and Bohemia, addressing cognitive and narrative problems of the interaction of philosophy, historiography, and psychology with fiction and fine arts from the point of view of literature.